Does upwelling intensity determine larval fish habitats in upwelling ecosystems? The case of Senegal and Mauritania. (19th June 2017) - Tiedemann, Maik; Fock, Heino O.; Brehmer, Patrice; Döring, Julian; Möllmann, Christian
Abstract: European sardine ( Sardina pilchardus ) and round sardinella ( Sardinella aurita ) comprise two‐thirds of total landings of small pelagic fishes in the Canary Current Eastern Boundary Ecosystem (CCEBE). Their spawning habitat is the continental shelf where upwelling is responsible for high productivity. While upwelling intensity is predicted to change through ocean warming, the effects of upwelling intensity on larval fish habitat expansion is not well understood. Larval habitat characteristics of both species were investigated during different upwelling intensity regimes. Three surveys were carried out to sample fish larvae during cold (permanent upwelling) and warm (low upwelling) seasons along the southern coastal upwelling area of the CCEBE (13°–22.5°N). Sardina pilchardus larvae were observed in areas of strong upwelling during both seasons. Larval habitat expansion was restricted from 22.5°N to 17.5°N during cold seasons and to 22.5°N during the warm season. Sardinella aurita larvae were observed from 13°N to 15°N during cold seasons and 16–21°N in the warm season under low upwelling conditions. Generalized additive models predicted upwelling intensity driven larval fish abundance patterns. Observations and modeling revealed species‐specific spawning times and locations, that resulted in a niche partitioning allowing species' co‐existence. Alterations in upwelling intensity may have drastic effects on the spawning behavior, larval survival, and probably recruitment success of a species. The results enable insights into the spawning behavior of major small pelagic fish species in the CCEBE. Understanding biological responses to physical variability are essential in managing marine resources under changing climate conditions.